An empirical study on the importance of technology quality in creating brand preference among the Generation Y (Gen-Y) banking customers in Kerala - Dr.A.Sukumaran, P.Ravindranath*, (International Journal of Scientific Research and Management (IJSRM), 2016)
The objective of this study was to understand the various determinants that develop satisfaction among Generation Y (Gen-Y) banking customers, and to find out the relative importance of technology in creating brand preference among them. Responses from 400 Gen-Y banking customers in Cochin were collected using a structured questionnaire to examine the role of various determinants to customer satisfaction. The study also envisaged to examine the influence of risk perceptions in moderating the satisfaction feel of Gen-Y in technology enabled service delivery.  The data collected were analyzed using structural equation approach using a PLS based tool. The study identified important predictors of service quality in the perceptions of Gen-Y as technology quality and brand image. The human dimension was viewed by Gen-Y as less important. The observation regarding the absence of risk perception in using technology enabled applications truly portrayed the Gen-Y behaviour towards technology usage. Further, it was observed that in perceiving technology quality Gen-Y expects maximum technology enabled applications with minimum service